Mathematical Critical Thinking Abilities of Middle School Students in Tidore Based on Gender and Background - Arwan Mhd Said; Dana Arif Lukmana (International Journal of Trends in Mathematics Education Research, 2020)
This study was conducted to answer the question, "What is the description of the mathematical critical thinking ability of middle school students in Tidore city based on gender and background?". This question is essential to answer because it is motivated by the mathematical performance of students in Tidore is low nationally and is reinforced by the results of the 2015 and 2018 PISA and OECD surveys. Gender is used as a distinguishing factor because this factor is still culturally rooted in this area and affects the role of society in life socially. Tidore comprises three significant communities, namely coastal, urban, and mountainous communities, each of which has a unique pattern of social life. Therefore, researchers also use "background" as a distinguishing factor. Data collection was carried out in three schools representing the three communities using a questionnaire, math problems (arithmetic, geometry, algebra), and semi-structured interviews on two subjects (male and female) in each location. The results of the analysis show, based on gender and background the ability of students to think critically mathematically are categorized as sufficient (close to less) with a mathematical critical thinking (MCT) achievement ratio of  0.27. Male subjects had an achievement ratio of 0.3 (sufficient) higher than female subjects of  0.24 (insufficient). Based on the background subjects from urban areas had the highest MCT achievement ratio of 0.49 (sufficient) while the subject achievement ratio of the coast and mountains were 0.17 (insufficient) and 0.15 (insufficient), respectively.